SEASONAL CHANGES OF WATER TEMPERATURE AND CHLOROPHYLL CONCENTRATION IN LAKE O-IKE (Eleventh Symposium on Polar Biology) - オオヤマ, ヨシクニ; モリモト, ケンジ; モチダ, ユキラ; OHYAMA, Yoshikuni; MORIMOTO, Kenji; MOCHIDA, Yukira (National Institute of Polar Research, 1990)
P(論文) Seasonal observations of water temperature and chlorophyll concentration were carried out in Lake 6-ike near Syowa Station, Antarctica, in 1987. Water sampling was begun at the end of March and continued to the next January almost every month. The lake surface was covered with ice during 10 months from March to December. The lake water was cooled through surface from March to August, but the bottom water remained above 3℃ even at the coldest season. According to the results of chlorophyll measurement, the bloom of phytoplankton seemed to occur at two times in April and September mainly at lower layer reaching 0.80 and 1.82mg/m^3, respectively. departmental bulletin paper